Effect of Improper Curing on the Properties of Normal Strength Concrete - Memon, R. P.; Sam, A. R. M.; Awang, A. Z.; Memon, U. I. (Engineering, Technology & Applied Science Research, 2018)
In real applications, 28 days are regarded as proper curing time for concrete. There is a self-evident need to minimize the duration of curing days. For this purpose, this research investigates 1 to 7 days of curing and compares it with concrete cured for 28 days. Three grades of normal concrete strength grade 30, grade 35 and grade 40 were made. After curing, two exposure conditions were applied to the concrete, inside laboratory-controlled environment and outside environment. Results indicate that slump increases with cement content in DOE method at constant water content. The concrete density in all grades reduces when the concrete is subject to inside exposure in comparison with outside exposure. Water loss from concrete reduces with increase in curing days in all concrete grades. Compression strength of all concrete grades increases with increase in curing days. For the uniformity of concrete, ultrasonic pulse velocity indicated that with an increase in curing days, concrete becomes denser and a bit void. Results showed that an increase in curing days also improves the surface quality of concrete. The significance point noticed is that there was not much difference in the concrete properties between 7 days of curing and 28 days of curing in all grades.